2019
DOI: 10.21278/brod70206
|View full text |Cite
|
Sign up to set email alerts
|

Design and Model Test of Structural Monitoring and Assessment System for Trimaran

Abstract: Due to the unique structural design of multihull, the structural response on trimaran is often more complex than the response of monohull in navigation. In order to ensure the safety of trimaran navigation and predict the potential damage of local structure, the structure monitoring technology is applied. According to the structural characteristics of trimaran, structural monitoring and assessment system for multihull is designed and introduced in detail, and corresponding model test is taken to demonstrate it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For the preliminary design of the trimaran, the state of the art was taken into account. Recent investigations on the design of trimaran have researched the structure [35][36][37][38], the…”
Section: Not Implemented Properlymentioning
confidence: 99%
See 2 more Smart Citations
“…For the preliminary design of the trimaran, the state of the art was taken into account. Recent investigations on the design of trimaran have researched the structure [35][36][37][38], the…”
Section: Not Implemented Properlymentioning
confidence: 99%
“…For the preliminary design of the trimaran, the state of the art was taken into account. Recent investigations on the design of trimaran have researched the structure [35][36][37][38], the outrigger layout [39][40][41][42], optimization to reduce resistance [42][43][44][45], seakeeping and stability performances [46][47][48], and the design method itself [49][50][51]. From a structural point of view, Daidola et al [35] discussed preliminary structural design procedures for a large highspeed sealift trimaran, while Tang et al [36] applied structure monitoring technology, and Jia et al [37] proposed a lightweight design of a trimaran bulkhead using structural topology optimization.…”
Section: Not Implemented Properlymentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of the trimaran studied for this paper is to have an smaller floating area rather than its equivalent monohull, as well as a smaller longitudinal inertia moment and a longitudinal metacentric height (Riola and Perez 2012) [23] (Tang, 2019) [28].…”
Section: Fig 6 Representative Of the Sea Condition Chartsmentioning
confidence: 99%
“…They concluded that warping-based theory provides a better model of the behaviour of prismatic thin-walled sections because longitudinal deformation is considered. Tang et al [8] used three real-time structural strength assessment methods to identify hull longitudinal strength, yield local strength, and fatigue strength. The system evaluates short-and long-term structural strength.…”
Section: Introductionmentioning
confidence: 99%